2023
DOI: 10.3389/fnins.2023.1227081
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning analysis reveals aberrant dynamic changes in amplitude of low-frequency fluctuations among patients with retinal detachment

Abstract: BackgroundThere is increasing evidence that patients with retinal detachment (RD) have aberrant brain activity. However, neuroimaging investigations remain focused on static changes in brain activity among RD patients. There is limited knowledge regarding the characteristics of dynamic brain activity in RD patients.AimThis study evaluated changes in dynamic brain activity among RD patients, using a dynamic amplitude of low-frequency fluctuation (dALFF), k-means clustering method and support vector machine (SVM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Similarly, Huang et al 6 found a decrease in the ReHo value of L-MFG in patients with RD, suggesting cognitive impairment in these individuals. Our previous study revealed an increase in the dynamic ALFF values of the bilateral MFG and the right inferior frontal gyrus (IFG) in patients with RD 9 , which aligns with our current research. Patients who experience RD face challenges in adapting to monocular vision due to the sudden loss of vision.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similarly, Huang et al 6 found a decrease in the ReHo value of L-MFG in patients with RD, suggesting cognitive impairment in these individuals. Our previous study revealed an increase in the dynamic ALFF values of the bilateral MFG and the right inferior frontal gyrus (IFG) in patients with RD 9 , which aligns with our current research. Patients who experience RD face challenges in adapting to monocular vision due to the sudden loss of vision.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there were increased dEC values from the R-MOG to the R-V1, from the R-CAL to the R-V1, from the L-CUN to the R-V1, from the L-PCUN to the L-V1, as well as a decrease in bidirectional dEC values between the L-V1 and the R-PCUN. Kang et al 29 9 . The occipital lobe plays a primary role in perceiving and processing visual information, making it crucial in complex visual perception processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations